Mendefinisi semula makna kualiti hidup masyarakat bandar dalam konteks ilmu sosial - Azahan Awang; Abdul Samad Hadi; Jamaluddin Md. Jahi; Asmah Ahmad; Abdul Hadi Harman Shah (Environmental Management Society, Malaysia, 2006)
Re-defining the meaning of quality of life amongst urban society is a small contribution in social knowledge that is applicable to environmental management in Malaysia. Most working definitions of quality of life are confined to the totalling up of urban environment infrastructure facilities. It is assumed that if the facilities are good, then the quality of life is also good although in reality it is a mere assumption. This article argues that quality of life is not static in its meaning, even if it is in the same environment. In reality quality of life is defined by experiences beside what is provided for by the environment. In such a case quality of life provides a negotiated meaning. An empirical study was carried out in Seremban to determine the status of quality of life of its population. The result of the study is deeply induced to determine the meaning of quality of life of the urban population to be applied to the field of social knowledge and environmental management in Malaysia. Re-defining quality of life does not mean the present working definition is not utilised, but resident’s perception, needs and objectives makes the definition of quality of life to carry a different meaning